INVESTIGATION OF THE FIBRINOLYTIC-ACTIVITY OF DEFIBROTIDE FRACTIONS - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1994)
1. Defibrotide is a drug which is a mixture of DNA fragments of various lengths. To characterize the active component which is responsible for the fibrinolytic effect, we fractionated defibrotide by column chromatography and investigated direct and endothelium dependent fibrinolytic activity of the major fractions by euglobulin lysis time (ELT) measurements. 2. Defibrotide and its fractions added to human plasma samples did not change ELT. However addition of conditioned media of human umbilical vein endothelial cell cultures which were incubated with defibrotide or its high molecular weight fractions shortened the ELT significantly (P < 0.001), whereas small molecular weight fractions did not effect the ELT. 3. Our results show that high molecular weight defibrotide fractions have fibrinolytic activity and the effect is endothelium dependent.
Keywords: DEFIBROTIDE; FIBRINOLYSIS; EUGLOBIN LYSIS TIME; ENDOTHELIUM; PROSTACYCLIN